Cactus-like structure of BP@MoS2 hybrids: An effective mechanical reinforcement and flame retardant additive for waterborne polyurethane. (August 2022) - He, Lingxin; Chu, Fukai; Zhou, Xia; Song, Lei; Hu, Yuan
Highlights: A novel cactus-like structure of BP@MoS2 hybrids was designed and synthesized. The tensile strength and fracture strength of WPU/BP@MoS2 -2.0 increase by 57.7% and 36.5%. The PHRR and TSP of WPU/BP@MoS2 -2.0 reduce by 50.3% and 52.0%. BP and MoS2 have a cooperative effect in suppressing the heat release behavior of WPU/BP@MoS2 . Abstract: Design novel flame retardant and mechanical enhancing agents of waterborne polyurethane (WPU) is a crucial issue for expanding its application. Herein, BP@MoS2 hybrids was designed and prepared to enhance the fire safety and mechanical properties of WPU and BP@MoS2 possessed a novel cactus-like structure. BP@MoS2 was prepared in a two-step method including preparation of black phosphorus (BP) sheets by chemical vapor transfer method and preparation of BP@MoS2 by in situ growth of molybdenum disulfide (MoS2 ). with adding 2.0wt% BP@MoS2, the tensile strength and fracture strength of WPU/BP@MoS2 -2.0 increase by 57.7% and 36.5%, respectively. The peak value of heat release rate (PHRR) and total smoke production (TSP) of WPU/BP@MoS2 -2.0 also reduce by 50.3% and 52.0%, which indicates that fire safety and mechanical performance of WPU/BP@MoS2 -2.0 is effectively enhanced. Meanwhile, BP@MoS2 has both condensed phase and gas phase flame retardant effect on WPU. In condensed phase, the residue char of WPU/BP@MoS2 is with excellent physical barrier effect. In gas phase, BP@MoS2 can inhibit the generation of flammable volatiles such as aromatic and aliphatic compounds during burning of WPU/BP@MoS2, thereby inhibiting the heat release and smoke release behavior of WPU/BP@MoS2 . Graphical abstract: Image, graphical abstract